2018
DOI: 10.2196/preprints.13229
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Hospital-Community-Family–Based Telehealth Program for Patients With Chronic Heart Failure: Single-Arm, Prospective Feasibility Study (Preprint)

Abstract: BACKGROUND An increasing number of patients with chronic heart failure (CHF) are demanding more convenient and efficient modern health care systems, especially in remote areas away from central cities. Telehealth is receiving increasing attention, which may be useful to patients with CHF. OBJECTIVE This study aimed to evaluate the feasibility of a hospital-community-family (HCF)–based telehealt… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…The analysis showed that studies on the use of mobile applications were conducted in the USA (n=7) ( 30 - 36 ), Sweden (n=3) ( 37 - 39 ), Republic of Korea (n=1) ( 40 ), Brazil (n=1) ( 41 ), Norway (n=2) ( 42 , 43 ), Switzerland (n=1) ( 44 ), Belgium (n=1) ( 45 ), China (n=9) ( 22 , 46 - 53 ), Romania (n=1) ( 54 ), Japan (n=1) ( 55 ), Finland (n=1) ( 24 ), France (n=1) ( 56 ), New Zealand (n=1) ( 57 ), Iran (n=2) ( 58 , 59 ), Georgia (n=1) ( 60 ), Spain (n=2) ( 61 , 62 ), Palestine (n=1) ( 63 ) and Germany (n=3) ( 64 - 66 ). Two studies were conducted simultaneously in India (n=2) ( 67 , 68 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The analysis showed that studies on the use of mobile applications were conducted in the USA (n=7) ( 30 - 36 ), Sweden (n=3) ( 37 - 39 ), Republic of Korea (n=1) ( 40 ), Brazil (n=1) ( 41 ), Norway (n=2) ( 42 , 43 ), Switzerland (n=1) ( 44 ), Belgium (n=1) ( 45 ), China (n=9) ( 22 , 46 - 53 ), Romania (n=1) ( 54 ), Japan (n=1) ( 55 ), Finland (n=1) ( 24 ), France (n=1) ( 56 ), New Zealand (n=1) ( 57 ), Iran (n=2) ( 58 , 59 ), Georgia (n=1) ( 60 ), Spain (n=2) ( 61 , 62 ), Palestine (n=1) ( 63 ) and Germany (n=3) ( 64 - 66 ). Two studies were conducted simultaneously in India (n=2) ( 67 , 68 ).…”
Section: Resultsmentioning
confidence: 99%
“…In terms of application, mobile applications were designed for patients with diagnoses such as heart failure ( 24 , 46 , 58 ), supraventricular tachycardia ( 30 , 33 ), cardiac arrest ( 37 ), acute coronary syndrome ( 39 , 68 ), hypertension ( 31 , 35 , 41 , 59 - 61 , 63 ), ischemic heart disease ( 36 , 48 , 69 ), coronary artery disease ( 45 , 65 ) or after coronary artery bypass grafting ( 51 ), myocardial infarction ( 38 , 49 , 50 ), atrial fibrillation ( 52 , 55 ), obstructive coronary artery disease ( 70 ), ( 47 ) and general CVD ( 32 , 40 , 53 , 54 , 62 , 64 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations